2014
DOI: 10.1093/cvr/cvu257
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting abdominal aortic aneurysm in Ang II-infused mice: suprarenal branch ruptures and apparent luminal dilatation

Abstract: Our results are the first to describe apparent luminal dilatation, suprarenal branch ruptures, and intramural haematoma formation in dissecting abdominal aortic aneurysms in mice. Moreover, we validate and demonstrate the vast potential of phase contrast X-ray tomographic microscopy in cardiovascular small animal applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 40 publications
6
77
0
Order By: Relevance
“…These findings are consistent with findings in human AD 18. Continued aortic stress activates proliferative and inflammatory responses, and these responses occur in parallel with the development of focal medial disruption to the aorta 15. We found that in WT mice, focal medial disruption of the aorta seldom led to the development of AD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with findings in human AD 18. Continued aortic stress activates proliferative and inflammatory responses, and these responses occur in parallel with the development of focal medial disruption to the aorta 15. We found that in WT mice, focal medial disruption of the aorta seldom led to the development of AD.…”
Section: Discussionsupporting
confidence: 91%
“…At 1 week after starting Ca+AngII treatment, most of the WT and mSocs3‐KO mice developed no AD. However, closer observation revealed a slight thickening of the aortic wall at the branching point of the celiac trunk or the superior mesenteric artery (Figure 1A and 1B; Video S1), as reported previously 15, 17. Histological examination showed that the thickened portion of the aorta contained cellular infiltration and fibrosis.…”
Section: Resultssupporting
confidence: 83%
“…This hypothesis was initially based on observations of Gavish et al, who reported focal ruptures of the elastic lamellae in 126 of 325 investigated histological sections that included at least part of a branch orifice, but in none of the 479 sections in between branches [3]. The branch-related hypothesis was further supported by our previous work, in which we used a novel post mortem imaging technique (PCXTM) to visualize abdominal aortic aneurysms in angiotensin II-infused mice [4]. We demonstrated that the variation in aneurysm shape, ranging from Grade I (minor dilatation without thrombus) to Grade IV (polymorphic aneurysm extending into the thoracic aorta) [37,38], was directly related to the number and location of focal mechanical failures of the tunica media that occurred in the vicinity of aortic side branches.…”
Section: Fsi Model Predictions Versus Pcxtm Observationsmentioning
confidence: 67%
“…Our high-resolution post mortem images showed that the intramural hematoma was related to ruptures in the tunica media near suprarenal side branches (such as intercostals and the superior suprarenal artery). Moreover, apparent luminal dilatation could be linked to a tear in the tunica media that appeared caudal, cranial or left lateral to the celiac artery [4].…”
Section: An Animal-specific Fsi Model Of the Abdominal Aorta In Anestmentioning
confidence: 99%
“…5, panel A). Moreover we have recently demonstrated the previously undetected role of small branches in the early phase of cardiovascular pathology (Trachet et al, 2014a). Therefore, we decided to include the cerebral tree and other small branches in the model, despite the lack of proper validation.…”
Section: Model Validation In Small Side Branchesmentioning
confidence: 99%